2010
DOI: 10.1161/circulationaha.109.928796
|View full text |Cite
|
Sign up to set email alerts
|

Mobilized Human Hematopoietic Stem/Progenitor Cells Promote Kidney Repair After Ischemia/Reperfusion Injury

Abstract: Background-Understanding the mechanisms of repair and regeneration of the kidney after injury is of great interest because there are currently no therapies that promote repair, and kidneys frequently do not repair adequately. We studied the capacity of human CD34 ϩ hematopoietic stem/progenitor cells (HSPCs) to promote kidney repair and regeneration using an established ischemia/reperfusion injury model in mice, with particular focus on the microvasculature. Methods and Results-Human HSPCs administered systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
155
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(172 citation statements)
references
References 55 publications
14
155
0
2
Order By: Relevance
“…In the present study, we found that compared with the sham control, the protein expression of apoptotic biomarkers (ie, mitochondrial Bax, cleaved caspase 3 and PARP) were markedly enhanced in the acute IR kidney. Our findings, therefore, corroborated the findings from previ- [19][20][21][22][23]28] . The protein expression of these apoptotic parameters was down-regulated after administration of a low dose of sitagliptin and they were further down-regulated after higher dose of sitagliptin treatment.…”
Section: Wwwnaturecom/apssupporting
confidence: 90%
See 3 more Smart Citations
“…In the present study, we found that compared with the sham control, the protein expression of apoptotic biomarkers (ie, mitochondrial Bax, cleaved caspase 3 and PARP) were markedly enhanced in the acute IR kidney. Our findings, therefore, corroborated the findings from previ- [19][20][21][22][23]28] . The protein expression of these apoptotic parameters was down-regulated after administration of a low dose of sitagliptin and they were further down-regulated after higher dose of sitagliptin treatment.…”
Section: Wwwnaturecom/apssupporting
confidence: 90%
“…Mitochondrial damage [20][21][22] and cellular apoptosis [19,21,28] have also been reported to be frequent findings after IR injuries in solid organs. In the present study, we found that compared with the sham control, the protein expression of apoptotic biomarkers (ie, mitochondrial Bax, cleaved caspase 3 and PARP) were markedly enhanced in the acute IR kidney.…”
Section: Wwwnaturecom/apsmentioning
confidence: 99%
See 2 more Smart Citations
“…PTC density was analyzed as described with some modifications. 32 In brief, images (3200) were captured from CD31-stained sections (20 images per mouse). Each image was divided into 266 squares by a grid.…”
Section: Tissue Preparation and Histologymentioning
confidence: 99%